Strategi Dakwah Islam dengan Lagu Qur-any di Era Society 5.0 - Siti Hesniyatul Jamila (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2026)
Allah's knowledge is very much, while the time given by Allah is very short, this is as the educational value of QS. 18: 10 and QS. 31: 27. In addition, in the song Qur-any contains Islamic teachings that are not directly expressed by the author in his interpretation, namely the teachings of Tauhid, the first Tauhid Uluhiyah, Tauhid Rububiyah and Tauhid Dzat and His names, as well as the teachings of Sufism which are also contained in it, namely Khauf, Raja ', Syukur, Mahabbah, Wara' and Zuhud. Therefore, the researcher wants to describe how the strategy of Islamic da'wah with the song Qur-any in the era of society 5.0 and what are the titles of the songs Qur-any by Abah KH. Drs. M. Qoyim Ya'qub. This research method uses a qualitative approach with library research. The data sources are scientific texts analyzed using content analysis. Research results: The Qur-any song can be used as a medium for Islamic da'wah either directly or through social media access, for example, such as a YouTube account, and can be taught in educational institutions in Indonesia, both taught in the classroom learning process and in extracurricular activities because the Qur-any song is under the auspices of the national education foundation, the IMTAQ Educators Association (IPdI) Surabaya, SK MENKUMHAM: AHU-06844.50.10.2014 Jln. Gayung Kebonsari XV / 1, Surabaya, and the IPdI organization belongs to all educational institutions. There are 6 volumes of Quran songs including Vol I with 10 songs, namely This Life, Beware of Temptation, The World as a Means, The Greatest Blessing, Ulama’, Forgive the Layman, Knowledge that is Beneficial, Drugs, Become a Robbi Person, Yoo Ngaji Al-Qur’an. Vol II has 9 songs, namely Love Faith, Give Syafa’at, Your Name is God, Praise is Only for God, Yaa Rohman, Allah is the Ruler, In You God, Guide Us, Alif Lam Mim. Vol III has 9 songs, namely No Doubt, The Quran is a Guide, We are Afraid of Threats, I Take Refuge, O My Heart, Abu Lahab Perishes, When Help Comes, O infidels, Many Blessings. Vol IV has 11 songs, namely Struggle, What Are We, The Routine, The Miraculous, Our Bodies Strive, We Cultivate Hearts, Interpretation of the Quran, God’s Law, Four Kinds of Punishment, The Heaviest Punishment, Prayer. Vol V has 13 songs, namely Zakat, Fasting, Hajj, Haram Food, Inheritance, Business Prohibition, Approaching Adultery, Marriage, Don't Kill Children, Women, Hijab, Choose a Leader, Morals. Vol VI has 6 songs, namely Prioritize Morals, Avoid Finding Fault in People, Become a Ustadz, Heaven, Names of Prophets, Names of Angels. Ilmu Allah sangatlah banyak, sedangkan waktu yang diberikan Allah sangatlah sebentar, hal ini sebagaimana nilai pendidikan QS. 18: 10 dan QS. 31: 27. Selain itu, dalam lagu Qur-any mengandung tentang ajaran Islam yang tidak diungkapkan langsung oleh pengarang dalam penafsirannya yaitu adanya ajaran Tauhid, yang pertama Tauhid Uluhiyah, Tauhid Rububiyah dan Tauhid Dzat dan nama-nama-Nya, serta ajaran Tasawuf yang juga terkandung di dalamnya yaitu Khauf, Raja’, Syukur, Mahabbah, Wara’ dan Zuhud. Oleh karena itu, peneliti ingin mendeskripsikan bagaimana strategi dakwah Islam dengan lagu Qur-any di era society 5.0 dan apa saja judul lagu Qur-any karya Abah KH. Drs. M. Qoyim Ya’qub. Metode penelitian ini menggunakan pendekatan kualitatif dengan jenis library research. Sumber datanya berupa teks-teks ilmiah yang dianalisis menggunakan content analisys. Hasil penelitian : Lagu Qur-any bisa dijadikan media dakwah Islam baik secara langsung maupun melalui akses media sosial misalnya seperti akun youtube, serta bisa diajarkan di lembaga pendidikan yang ada di Indonesia, baik diajarkan dalam proses pembelajaran di kelas maupun pada kegiatan ekstrakurikuler karena lagu Qur-any berada di bawah naungan yayasan pendidikan nasional Ikatan Pendidik IMTAQ (IPdI) Surabaya SK MENKUMHAM: AHU-06844.50.10.2014 Jln. Gayung Kebonsari XV/1, Surabaya, dan organisasi IPdI milik semua lembaga pendidikan. Lagu Qur-any ada 6 Vol meliputi Vol I ada 10 lagu yaitu Hidup Ini, Waspada godaan, Dunia Tuk Sarana, Nikmat Paling Agung, Ulama’, Maafkan Orang Awam, Ilmu Yang Manfaat, Narkoba, Jadi Orangnya Robbi, Yoo Ngaji Al-Qur’an. Vol II ada 9 lagu yaitu Cintakan Keimanan, Beri Syafa’at, Nama-Mu Tuhan, Pujian Hanya Tuk Tuhan, Yaa Rohman, Allah Penguasa, Pada-Mu Tuhan, Bimbing Kami, Alif Lam Mim. Vol III ada 9 lagu yaitu Tiada ragu, Qur’an Petunjuk, Kita Takut Ancaman, Kuberlindung, Wahai Hatiku, Binasa Abu Lahab, Bila Datang Pertolongan, Hai kafir, Nikmat yang Banyak. Vol IV ada 11 lagu yaitu Berjuang, Apa Kita, Yang Rutin, Yang Ajaib, Jasad Kita Berusaha, Kita Membina Hati, Tafsir Qur’an, Hukum Tuhan, Empat Macam Hukuman, Hukuman Terberat, Sholat. Vol V ada 13 lagu yaitu Zakat, Puasa, Haji, Makanan Haram, Waris, Larangan Bisnis, Mendekati Zina, Menikah, Jangan Bunuh Anak, Wanita, Jilbab, Pilih Pemimpin, Akhlak. Vol VI ada 6 lagu yaitu Dulukan Akhlak, Hindari Cari Salah Orang, Jadi Ustadz, Surga, Nama-Nama Nabi, Nama-Nama Malaikat.